Gordailu and pedagogic renovation in the Basque Country. Politics and education during the late francoism - Ander DELGADO CENDAGORTAGALARZA (Ediciones Universidad de Salamanca, 2017)
This article analyses the educative and pedagogical renovation proposals situated in their social and economic context. Thus, it intends to obtain a wider vision of the problems or helps these proposals may have when it comes to their application in schools. It will be of major consideration to differentiate within these proposals the aspects related with classroom management from other approaches related with the goals to transform the society through a reformed education, that sometimes appear inside them, to understand better their social reception. This article is centred on the research of proposals based on the ideas Paulo Freire tried to introduce in the ikastola or Basque schools in the seventies of the last Century in the Basque Country and the problems they found when their application was intended.